Relevansi Tafsir Kontekstual dalam Menjawab Masalah Sosial-Kemasyarakatan di Abad 21 - Muhammad Halif Asyroful Bahana (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2024)
Contextual interpretation, developed by Abdullah Saeed, is a relevant approach in dealing with societal problems in the 21st century. This method does not only focus on the text of the Qur'anic verse, but also understands the micro, macro, and social development, culture, and circumstances of today. Thus, contextual tafsir can provide alternative solutions to socio-religious problems faced by contemporary society.